"Truth be told" – Semantic memory as the scaffold for veridical communication. (22nd January 2018) - Hayes, Brett K.; Ramanan, Siddharth; Irish, Muireann
Abstract: Theoretical accounts placing episodic memory as central to constructive and communicative functions neglect the role of semantic memory. We argue that the decontextualized nature of semantic schemas largely supersedes the computational bottleneck and error-prone nature of episodic memory. Rather, neuroimaging and neuropsychological evidence of episodic-semantic interactions suggest that an integrative framework more accurately captures the mechanisms underpinning social communication.